Simultaneous Altitude and RCS Estimation with Propagation Attenuation in Bistatic HFSWR - Zhao Kongrui; Yu Changjun; Zhou Gongjian; Quan Taifan (International Journal of Antennas and Propagation)
High frequency surface wave radar (HFSWR) is traditionally unable to detect target altitude information. To simultaneously estimate the target altitude and radar cross-sections (RCS) with bistatic HFSWR, a novel estimation model is proposed with the variation of the propagation attenuation, and the target echoes are utilized to construct the measurement equation. The presented model is completely observable to the target state, which can contribute to preferable estimation results. In order to improve the estimation accuracy, a centralized fusion model is adopted to fuse four measurement vectors. Simulations and practical examples demonstrate the effectiveness of the proposed estimation model.